Software Engineering: A Practitioner's Approach - Roger S. Pressman; Bruce R Maxim (India Mc Graw Hill, 2023)
For almost four decades, Software Engineering: A Practitioner's Approach (SEPA) has been the world's leading textbook in software engineering. The ninth edition represents a major restructuring and update of previous editions.
Keywords: Engineering; Software Engineering